Multiple Energy Transfer Channels in Rare Earth Doped Multi‐Exciton Emissive Perovskites - Huwei Li; Kai Han; Zheyu Li; Hongxia Yue; Xinyu Fu; Xinyu Wang; Zhiguo Xia; Shuyan Song; Jing Feng; Hongjie Zhang (Advanced Science, 2024)
Abstract Revealing the energy transfer (ET) process from excitons to rare earth ions in halide perovskites has great guiding value for designing optoelectronic materials. Here, the multiple ET channels in multi‐exciton emissive Sb3+/Nd3+ co‐doped Cs2ZrCl6 are explored to comprehend the ET processes. Förster–Dexter ET theory reveals that the sensitizer concentration rather than the overlap integral of the spectra plays the leading function in the comparison of the ET efficiency among multiple ET channels from the host self‐trapped excitons (STEs) and dopant triplet STEs to Nd3+ ions. Besides, Sb3+/Nd3+ co‐doped Cs2ZrCl6 enables varied color delivery and has great potential as anti‐counterfeiting material. Under X‐ray irradiation, Sb3+/Nd3+ co‐doped Cs2ZrCl6 presents a high light yield of ≈13300 photons MeV−1 and promising X‐ray imaging ability. This work provides new insight for investigating the ET efficiency among multiple ET processes and presents great potentiality of multi‐exciton emissive perovskites in the fields of anti‐counterfeiting and X‐ray imaging.